Modern algebra - Waerden, B.L. Van Der (New York Fredorick Ungar Publishing Co., 1953)
Modern algebra, also known as abstract algebra, is a branch of mathematics that studies algebraic structures, which are sets with operations defined on their elements. It moves beyond the familiar rules of elementary algebra to explore general properties of mathematical systems. Key algebraic structures include groups, rings, fields, and vector spaces.
Keywords: Algebra; Mathematics